Optimalisasi Pembelajaran Fisika Melalui Implementasi Simulasi PhET di SMA Negeri 7 Mataram - Aulia Aulia; Robiatul Adawiah; Lutfiatussolihah Lutfiatussolihah (Indonesian Journal of Education and Community Services, 2026)
Physics instruction still faces challenges in visualizing abstract concepts, particularly in schools with limited laboratory facilities. This situation results in students being less actively engaged in the learning process and struggling to grasp concepts regarding forms and transformations of energy. This community service initiative aimed to optimize physics instruction at SMA Negeri 7 Mataram by implementing PhET simulations for the topic of energy forms and transformations. The activity involved providing instructional support to 27 students from class XI A2, structured into preparation, implementation, and evaluation phases. Data were collected using observation sheets, student worksheets (LKPD), evaluation questions, and documentation, and were subsequently analyzed descriptively. The results indicate that the implementation of PhET simulations enhanced student engagement, evidenced by active participation in discussions, exploration of the simulations, and the ability to explain the relationships between energy forms and transformations based on their observations. Furthermore, the use of worksheets as exploration guides enabled students to better identify various forms of energy and explain energy transformation processes. Thus, the implementation of PhET simulations effectively supports more interactive physics instruction, aids in visualizing abstract concepts, and serves as a viable virtual laboratory alternative for physics learning in schools.